Lost in space: Caldwell Luc antrostomy for retrieving displaced root into maxillary sinus: a case report / Sara Luay Thanoon, Mohd Shawal Firdaus Mohamad and Luay Thanoon Younis - Luay Thanoon, Sara; Mohamad, Mohd Shawal Firdaus; Younis, Luay Thanoon (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
The palatal root of the first permanent molar is the most commonly deflected root into the maxillary sinus during extraction. A rational approach to the surgical removal of a root from the antrum is important. Some surgeons prefer the alveolar approach while others prefer the Caldwell-Luc operation. In this report, a case was presented where the palatal root tip of the right upper first molar was displaced into the right maxillary sinus during simple extraction of the tooth which was later successfully removed from the maxillary sinus by the Caldwell-Luc approach. CBCT was used to locate and remove the lost root tip.